2021
DOI: 10.1002/cphc.202000985
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Small Structural and Environmental Differences in Solids with 15N NMR Chemical Shift Tensors

Abstract: The ability to theoretically predict accurate NMR chemical shifts in solids is increasingly important due to the role such shifts play in selecting among proposed model structures. Herein, two theoretical methods are evaluated for their ability to assign 15N shifts from guanosine dihydrate to one of the two independent molecules present in the lattice. The NMR data consist of 15N shift tensors from 10 resonances. Analysis using periodic boundary or fragment methods consider a benchmark dataset to estimate erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…NMR parameters derived from the CS and EFG tensors have been used extensively in molecular structure refinement (Olsen et al, 2003;Witter et al, 2006;Harris et al, 2010;Apperley et al, 2012;Harper et al, 2013;Kalakewich et al, 2015;Yang et al, 2016;Soss et al, 2017;Chalek et al, 2021;Wang et al, 2021). Recently, plane-wave EFG tensor predictions involving 14 N, 17 O, and 35 Cl nuclei were used to obtain optimized damping parameters for crystal geometry refinement using Grimme's DFT-D2 scheme (Holmes and Schurko, 2018).…”
Section: Modeling Disorder In the 4-nitrobenzaldehyde Crystal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…NMR parameters derived from the CS and EFG tensors have been used extensively in molecular structure refinement (Olsen et al, 2003;Witter et al, 2006;Harris et al, 2010;Apperley et al, 2012;Harper et al, 2013;Kalakewich et al, 2015;Yang et al, 2016;Soss et al, 2017;Chalek et al, 2021;Wang et al, 2021). Recently, plane-wave EFG tensor predictions involving 14 N, 17 O, and 35 Cl nuclei were used to obtain optimized damping parameters for crystal geometry refinement using Grimme's DFT-D2 scheme (Holmes and Schurko, 2018).…”
Section: Modeling Disorder In the 4-nitrobenzaldehyde Crystal Structurementioning
confidence: 99%
“…SSNMR investigations are often coupled with X-ray diffraction and first-principals calculations to form the interdisciplinary field of NMR crystallography. The success of NMR crystallography has been greatly facilitated by the availability of accurate computational methods for predicting NMR parameters which typically employ density functional theory (DFT) (Gervais et al, 2005;Wu, 2008;Kong et al, 2013;Yang et al, 2016;Kong et al, 2017;Soss et al, 2017;Holmes and Schurko, 2018;Yamada et al, 2020;Chalek et al, 2021;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it has been reported that 15 N shift tensors exhibit a variation more than six times larger than 13 C sites. 18 A focus on 15 N has the further advantage of being relevant to protein structural refinement. Proteins are target structures of high interest because their experimental crystal structures are often much lower in resolution than comparable studies on small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[40] These efforts have proven particularly effective in improving the accuracy of fragment-based 15 N CS tensor calculations. [41,42] In the context of 51 V, a previous benchmark study identified electrostatic embedding as a crucial ingredient for accurate two-body fragment CS tensor calculations. [29] Specifically, two-body fragment calculations employing self-consistent point-charge embedding improved the accuracy of predicted 51 V isotropic chemical shifts by 20% relative to traditional planewave methods.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐consistent charge embedding models have been developed to improve the accuracy of predicted NMR parameters in situations where higher order contributions strongly influence the NMR observable [40] . These efforts have proven particularly effective in improving the accuracy of fragment‐based 15 N CS tensor calculations [41,42] . In the context of 51 V, a previous benchmark study identified electrostatic embedding as a crucial ingredient for accurate two‐body fragment CS tensor calculations [29] .…”
Section: Introductionmentioning
confidence: 99%